A review on natural convective heat transfer of nanofluids - Haddad, Zoubida; Öztop, Hakan Fehmi; Abu-Nada, Eiyad; Mataoui, Amina (Pergamon-Elsevier Science Ltd, 2012)
Nanofluids are considered to have great potential for heat transfer enhancement and are highly suited to application in practical heat transfer processes. Recently, several important studies were carried out to understand and explain the causes of the enhancement or control of heat transfer using nanofluids. The main aim upon which the present work is based is to give a comprehensive review on the research progress on the natural convective heat transfer characteristics of nanofluids for both single- and two-phase models. Both experimental and theoretical studies are reviewed for natural convection of nanofluids in different types of enclosures. (c) 2012 Elsevier Ltd. All rights reserved.
Keywords: Nanofluids; Natural convection; Heat transfer